Farming wellbeing through and beyond COVID‐19: Stressors, gender differences and landscapes of support. (17th February 2023) - Rose, David Christian; Budge, Hannah; Carolan, Michael; Hall, Jilly; Hammersley, Conor; Knook, Jorie; Lobley, Matt; Nye, Caroline; O'Reilly, Alexis; Shortland, Faye; Wheeler, Rebecca
Abstract: Although there has been a recent surge in research on drivers of poor farmer wellbeing and mental health, there is still a limited understanding of the state of wellbeing in farming communities around the world and how it can be best supported. This special issue seeks to extend our knowledge of how a combination of different stressors can challenge the wellbeing of farmers, farming families and farm workers, as well as how negative impacts can be unevenly distributed between different individuals. We advance the state of the art in research on farmer wellbeing, illustrating how social, economic and environmental policy drivers combine to create multiple points of stress, which are experienced differently by different individuals (e.g., age, gender). We move beyond an exploration of stressors towards a consideration of how landscapes of support for farmer wellbeing, and packages of support interventions, can improve the social resilience of farming communities. To be effective, these landscapes of support need to be accessible, well‐funded, joined‐up, and adaptable to evolving crises. This special issue explores farmer wellbeing in the context of global agricultural transitions, which are demanding new ways of farming (e.g., digitalisation, net zero, economic restructuring), and in light of shock events, such as the COVID‐19 pandemic, in four countries—Ireland, New Zealand, the UK and the US. In exploring the impacts of future shock events and agricultural transitions on wellbeing, the issue concludes with a call to move beyond broad compilations of stressors and interventions and towards nuanced investigations of why and how poor farmer wellbeing occurs and how it can be best supported in specific contexts. The research from these four countries has wide relevance across European countries (similarity in farming systems, noting some differences), but a key message from the issue is that stressors on farmer wellbeing can be highly context‐dependent according to place‐based social, environmental, economic and political issues.